SHOTGUN METAGENOMIC SEQUENCING FOR THE CHARACTERIZATION OF BACTERIAL COMMUNITIES ASSOCIATED WITH GAMMARUS LACUSTRIS FROM FRESHWATER ECOSYSTEMS IN KAZAKHSTAN - S. Suleymenova; M. Kumar; S. Nuralibekov; T. Sabyrzhan; Ye. Kassymbekov; M. Yessentureyeva; K. Isbekov; S. Assylbekova; V. Fefelov; B. Pangereyev; A. Kydyrmanov (Animal Health and Biosafety, 2026)
Bacterial communities associated with the freshwater amphipod Gammarus lacustris collected from six inland lakes and a reservoir in Kazakhstan were characterized by shotgun metagenomic sequencing. Gammarus were obtained from lakes and reservoirs representing a range of salinity conditions, and bacterial community composition was compared at the family and genus levels. Community diversity was evaluated using the Shannon and Simpson indices, whereas differences among sampling sites were examined by principal coordinate analysis (PCoA) based on Bray–Curtis dissimilarity and tested by permutational multivariate analysis of variance (PERMANOVA). Enterobacteriaceae and Nitrobacteraceae were the dominant bacterial families in most samples, but their relative abundances differed considerably among the studied ecosystems. Marked differences were also found at the genus level. Bradyrhizobium, Ralstonia, Pseudomonas, Aeromonas, and Acinetobacter occurred at different abundances among the sampling sites, indicating substantial variation in bacterial community composition. Shoktas Reservoir supported the greatest bacterial diversity, whereas Lake Khomutino had the lowest Shannon and Simpson diversity values. PCoA separated the samples only partially according to sampling site, and PERMANOVA detected no significant association between bacterial community composition and salinity. These observations indicate that salinity alone does not account for the differences among the microbial communities and suggest that local environmental conditions also influence the microbiota of G. lacustris. The present findings extend the limited information available on freshwater Gammarus-associated bacteria and represent a shotgun metagenomic characterization of bacterial communities associated with G. lacustris from freshwater ecosystems in Kazakhstan. The data reported here provide a useful reference for future ecological and microbiological investigations of freshwater Gammarus.